Change Management in Digital Transformation The South Tangerang City Government Agency - Mukroni, Mukroni; Sartika, Ika (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the implementation of change management in supporting digital transformation within the South Tangerang City Government, particularly in the adoption of the Electronic-Based Government System (SPBE). The research evaluates how change management strategies address key challenges such as employee resistance, low digital literacy, and weak change management frameworks. Methodology/Approach: A qualitative descriptive approach was employed, utilizing in-depth interviews with government officials, direct observations of SPBE implementation, and document analysis. The study assessed change management effectiveness based on leadership commitment, employee engagement, and institutional readiness. Results/Findings: The findings reveal that change management has not been systematically implemented, leading to inefficiencies in digital transformation efforts. While some technological advancements have been achieved, persistent challenges include lack of structured organizational change models and insufficient transformational leadership to drive cultural and operational shifts. Conclusions: South Tangerang’s digital transformation has progressed technologically but is limited by employee resistance and low digital readiness. Strong leadership, user-focused systems, and ongoing capacity building are essential for sustainable governance. Limitations: This study focuses solely on the South Tangerang City Government, which may limit the generalizability of findings to other regions. Additionally, the dynamic nature of digital transformation necessitates continuous evaluation beyond the scope of this research. Contribution: The study offers practical guidance to strengthen digital transformation through structured change management, capacity building, and transformational leadership for sustainable public governance.